Heavy rainfall patterns in Vietnam and their relation with ENSO cycles. (16th September 2015) - Gobin, A.; Nguyen, H. T.; Pham, V. Q.; Pham, H. T. T.
ABSTRACT: Heavy rainfall months of more than 450 mm occur in all 56 meteorological stations in eight climatic zones of Vietnam during the rainy season from April to September in the north (>20°N), from August to December in the centre and from May to November in the south (<12°N). The severity of an El Niño Southern Oscillation (ENSO) episode, expressed as the integral of sea surface temperature anomaly (SSTA) in the central tropical Pacific over the duration, shows a 4.6‐fold (2.3‐fold) increase in number of heavy rainfall months during La Niña (El Niño) per unit change in severity during the 1960–2009 period, suggesting a twin peak occurrence with both ENSO extremes. A heavy rainfall index (HRI) links heavy rainfall months to the rainy season duration, and allows evaluation of the rainfall severity per station, climatic zone and ENSO cycle. For the deltas and central climatic zones, seasonal rainfall and number of heavy rainfall months are significantly higher at the p < 0.05 level during La Niña than during El Niño episodes. Interpolated seasonal rainfall shows distinct differences between regions, with location having a larger effect than ENSO cycles on monthly rainfall amounts. Twenty‐year return monthly rainfall derived from generalized Pareto distributions for peak over thresholds range from 475 mm in the central highlands to 2185 mm in the central coast. The spatial and temporal patterns of heavy monthly rainfall help explain flooding and paddy inundation which occur at least twice as frequent during La Niña as compared to El Niño conditions, particularly in Central Vietnam. The relation of HRI with both 20‐year return levels and ENSO cycles offers opportunities for fast screening of impacts in a wider region of Southeast Asia. Because ENSO cycles have an impact on flooding and paddy inundation, it provides prospects for early warning, differentiated for different zones and rainfall regimes.